Exploring off‐flavour compounds in soy‐based meats: Mechanisms and removal methods - Nagassa, Merga; He, Shudong; Liu, Shuyun; Wang, Junhui; Cao, Xiaodong; Chen, Shuguan; Song, Jiazhen; Sun, Hanju (Flavour and fragrance journal, 2024)
Plant‐based meat is projected to address world‐wide meat shortage and supply–demand imbalances, potentially promoting the growth of sustainable diet choices. Soybean is a key ingredient to produce this alternative food, but the off‐flavours that naturally occur in soy can hinder its widespread acceptance among consumers. This review extensively elaborates on the primary compounds responsible for off‐flavours, their formation mechanisms, and removal techniques. Lipoxygenase oxidation–reduction, oleosins removal, adjustment extrusion conditions, and β‐cyclodextrin treatment were discussed. Fermentation mechanisms, solvent extraction, enzymes hydrolysis, flavouring, and controlling storage conditions were summarised. The most crucial, safe, and effective techniques were enzyme restriction, β‐cyclodextrin treatment in conjugation with phospholipase A2, and modification of the extrusion condition. The reviews provide a systematic summary of the development and prevention methods for the undesirable flavour of soy protein isolate and soy‐based meat products. This review provides a comprehensive summary of previous literature regarding the formation and elimination strategies of off‐flavours.